MOBILE VIDEO ROBOT BERBASIS PERSONAL COMPUTER (PC) - Muslikhin, Rahmat Hidayat, dan Laily Noor Ikhsanto (Pelita - Jurnal Penelitian Mahasiswa UNY, 2009)
The development of robotics as a branch of electronic disciplines increases along with humanneeds. This condition makes the robotic technology is important to be developed. The research ofStudent Union Grant (SUG) 2009 entitled “Personal Computer (PC) - Based Mobile Video Robot’’aims to (a) build a navigation software of robot motion control, (b) build a hardware for mobile videorobot unit and (c) know how it works.The mobile video robot software was designed by using Visual Basic 6.0 to build navigationon the PC monitor. This navigation was as a user interface between humans and robots. The user’scommand data was issued via the parallel port (DB25). The parallel port data output were put intoAT89S52 and processed based on the algorithm. The result of the process would control TX2B totransmit the data based on the user’s command. The process of a robot hardware productionconsisted of TX2B transmitter unit and robot unit. The robot unit contained the RX2B recipient,AT89S52 data processor, the ULN2004 driver and h bridge, 211C CMOS camera and a UT66 minivideo sender. Meanwhile, the production of TX2B transmitter hardware and the data processor wasthrough the flashing programs written in Assembler language to AT89S52.The result of this research shows that mobile video robot hardware was able to work withnavigation software in a synergy. The software design result of mobile video robot navigationdisplayed on a PC was able to control the robot motion and display the results of the video via aninternal TV tuner. The performance of the mobile video robot could explore the flat road for 32minutes. The maximum robot control range / radius were 8 meters. The optimum video radius wason 5 meters in VHF-H/PAL channel 12, while the average instruction response was 53 ms.Keywords: mobile video robots, PC, AT89S52, and TX2B/RX2.